Looking for a Learning Curve in EVAR Based on the Zenith Stent Graft - Kalteis, Manfred; Benedikt, Peter; Huber, Florian; Haller, Florian; Kastner, Manfred; Lugmayr, Herbert (International Journal of Angiology, 2012)
The purpose of this study was to report the learning curve of endovascular aneurysm repair (EVAR) based on the Zenith stent graft (Cook Medical Inc., Bloomington, IN). In the last 9 years, 101 patients were treated with a Zenith stent graft. To display the learning curve, a cumulative sum (CUSUM) failure analysis curve of the 30-day technical success rate was calculated. For detailed analysis, our EVAR patient cohort was chronologically divided into three groups. Technical and clinical results, basic patient parameters, and procedural data were compared. The CUSUM graph indicated an initial sharp rise within the first 35 cases and a plateau thereafter. The 30-day technical success rate significantly increased from the first to the second group (83 vs. 100%; p = 0.019), as did the primary technical success rate (66 vs. 97%; p = 0.001). EVAR based on the Zenith stent graft required ∼35 cases to reach a stably high rate of short-term technical success.
Keywords: abdominal aortic aneurysm; endovascular repair; endovascular procedure; EVAR; learning curve; Zenith stent graft; early results